Maternity at Extreme Ages of Reproductive Life: Maternal and Perinatal Morbidity and Mortality in West African Country (Benin) - ABOUBAKAR, MOUFALILOU; OGOUDJOBI, OGOURINDÉ MATHIEU (My University, 2018)
Objective: To study morbidity and mortality related to maternity at extreme ages of reproductive life in two teaching hospitals at Cotonou in West African country (Benin). Materials and methods: This was a descriptive retrospective cross-sectional study over a period of 9 months. It focused on the cases of women under 18 and over 35 years old. The variables studied were maternal and perinatal morbidity and mortality. The statistical analysis was performed using the software EPI INFO 3.5.4. Results: Of 5424 deliveries registered during the study period, 874 women (99 under 18 years and 775 above 35 years) were in extreme ages, the frequency of 16.1%. Early maternity was more common among students (51.4%) and late maternity in informal sector workers (84%). The main complications found were Immediate Post-Partum Haemorrhage (IPPH) and soft tissue lesions. Perinatal morbidity was high with 11.4% of new-born in apparent death status in early maternity and 2.8% in late maternity. Maternal vital prognosis was good in both subgroups. Perinatal mortality was high. Conclusion: Maternity at the extreme ages of reproductive life, whether early or late, remains a high risk maternity.
Keywords: Early maternity; Late maternity; Morbidity; Mortality